The effect of innovation clusters on investment attractiveness growth in Russia (Revista de Investigaciones Universidad del Quindío, 2022)
The issue of developing the most efficient approach of funding innovation actions at the present phase of the implementation of cluster policy in the Russia federation is highly important. Exotic direct investments contribute to the triggering the investment procedure in the global economy, indirectly resulting in a rise in sustainability and quality. This study aims to analyze the impact of innovation clusters in the Russian Federation throughout the growth of investment attractiveness and triggering exotic economic integration. The structural, logical, system-functional and comparative analysis are utilized to meet that aim. Given the results, regional investments’ methods on the basis of the cluster means greatly affect investment attractions from huge investors. Nonetheless, investments in individual huge organizations aren’t as constructive as anticipated. It seems completely rational to think that the outcomes of the present shortages of innovation financing are uneven. 2020 was rather challenging for business throughout the globe. The innovative businesses weren’t any exceptions, even though implementing and developing new tools didn’t end and quiche end in some arenas. The investigation of the special literature on the matter under observation permits us to conclude that it is absolutely vital to evaluate the issues of Russian cluster policy and the investment attractiveness of innovative clusters.
Keywords: Foreign economic integration; cluster policy; investment attractiveness; innovative development; cluster approach